Melatonin, BAG-1 and cortisol circadian interactions in tumor pathogenesis and patterned immune responses - George Anderson (Open Exploration Publishing Inc., 2023)
A dysregulated circadian rhythm is significantly associated with cancer risk, as is aging. Both aging and circadian dysregulation show suppressed pineal melatonin, which is indicated in many studies to be linked to cancer risk and progression. Another independently investigated aspect of the circadian rhythm is the cortisol awakening response (CAR), which is linked to stress-associated hypothalamus-pituitary-adrenal (HPA) axis activation. CAR and HPA axis activity are primarily mediated via activation of the glucocorticoid receptor (GR), which drives patterned gene expression via binding to the promotors of glucocorticoid response element (GRE)-expressing genes. Recent data shows that the GR can be prevented from nuclear translocation by the B cell lymphoma-2 (Bcl-2)-associated athanogene 1 (BAG-1), which translocates the GR to mitochondria, where it can have diverse effects. Melatonin also suppresses GR nuclear translocation by maintaining the GR in a complex with heat shock protein 90 (Hsp90). Melatonin, directly and/or epigenetically, can upregulate BAG-1, suggesting that the dramatic 10-fold decrease in pineal melatonin from adolescence to the ninth decade of life will attenuate the capacity of night-time melatonin to modulate the effects of the early morning CAR. The interactions of pineal melatonin/BAG-1/Hsp90 with the CAR are proposed to underpin how aging and circadian dysregulation are associated with cancer risk. This may be mediated via differential effects of melatonin/BAG-1/Hsp90/GR in different cells of microenvironments across the body, from which tumors emerge. This provides a model of cancer pathogenesis that better integrates previously disparate bodies of data, including how immune cells are regulated by cancer cells in the tumor microenvironment, at least partly via the cancer cell regulation of the tryptophan-melatonin pathway. This has a number of future research and treatment implications.